Body dissatisfaction in women's artistic gymnastics: A longitudinal study of psychosocial indicators. Issue 17 (2nd September 2017) - Neves, Clara Mockdece; Filgueiras Meireles, Juliana Fernandes; Berbert de Carvalho, Pedro Henrique; Schubring, Astrid; Barker-Ruchti, Natalie; Caputo Ferreira, Maria Elisa
ABSTRACT: Body dissatisfaction is prevalent in women's artistic gymnastics (WAG). Cross-sectional research points to social and individual risk factors, however it does not account for potential changes in body dissatisfaction during an athletic season. This study aimed to determine how gymnasts' body dissatisfaction, risk factors for eating disorders, media internalisation, perfectionism and mood state change during pre-competition, competition and post-competition seasons and to identify how these psychosocial indicators impact on body dissatisfaction during the athletic year. The sample consisted of 20 Brazilian elite women's artistic gymnasts aged 10–16 years. Data were obtained from a 9-month study using: Body Shape Questionnaire (BSQ); Eating Attitude Test-26; Sociocultural Attitudes Towards Appearance Questionnaire-3 (SATAQ-3); Multidimensional Perfectionism Scale (MPS); Brunel Mood Scale (BRUMS) and triceps and subscapular skinfolds. Body dissatisfaction was higher during the competition season and disordered eating, perfectionism and vigour values were higher in the pre-competition season. Disordered eating has been found as the strongest predictor of body dissatisfaction during all seasons, and mood state partly contributed to body dissatisfaction in the competitive season. Stakeholders should understand that body dissatisfaction and the prevalence of disordered eating may change over time.